“Aplicación de cepas nativas de metarhizium anisopliae (metch) y beauveria bassiana (bals) vuill., para el control de insectos en arroz irrigado en el bajo mayo” - Arévalo Rojas, Víctor Manuel (2006)
The cultivation of rice in the Bajo Mayo, it is affected during the vegetative phase for different insect pests, being the main ones: Tagosodes orizicolus (Muir), Cicadelids and Lissorhoptrus bosqi. These insects feed of the leaves and they destroy the roots, which cause retard in the growth of the plant. The objective was to evaluate the effect of the direct application, by application volley method, of the entomopathogen mushrooms (M. anisopliae and B. bassiana), on the population of insect pests and natural enemies. The dose of 4 Kg/Ha of the produced mushrooms was handmadely (concentration of 109 conidias/g), in 20 parcels of 5 000 m2 . 1 O parcels were distributed for each one of the mushrooms. The evaluation of the parcels was carried out later before and after the application and 1 O days; for such an effect, each field was divided in 5 blocks and each one of which 5 samples were evaluated (planUgolpe) at random, certain the quantity of dead insects and with presence of the sign (mushroom), as well as the level of infestation of pests with a qualitative scale of the O at the 5. The results show us that there were not significant statistical differences in the effect of the application on the population of insect pests; neither they were enemy natural affected by these mushrooms. An average of 5,02 was obtained; 1,75 and 3,35 affected individuals of T. orizicolus, cicadelids and Lissorhoptrus bosqi, respectively; while the average of natural control (witness) it was of 7, 10; 0,00 and 0,50 respectively. The populations of T. orizicolus and the cicadelids increased considerably, while that of Lissorhoptrus bosqi it presented variation for the estimate of their populational density, possibly for the technique of utilized sampling.